Preliminary Selection of Device Materials to Locally Transform Thermal into SFR Neutron Spectrum - N. Chrysanthopoulou; P. Savva; M. Varvayanni; C. Colin; C. Huot-Marchand; N. Catsaros (Science and Technology of Nuclear Installations)
The safe introduction of Generation IV (Gen IV) reactor concepts into operation will require extensive testing of their components. This must be performed under neutronic conditions representative of those expected to prevail inside the new reactor cores when in operation. In a thermal Material Testing Reactor (MTR) such neutronic conditions can be achieved by tailoring the prevailing neutron spectrum with the utilization of a device containing appropriate materials. In this work various materials are investigated as candidate components of a device that will be required in case that a thermal MTR neutron energy spectrum must be locally transformed, so as to imitate Sodium cooled Fast Reactor (SFR). Many nuclides have been examined with respect to only their neutronic behavior, providing thus a pool of neutronically appropriate materials for consideration in further investigation, such as regarding reactor safety and fabrication issues. The nuclides have been studied using the neutronics code TRIPOLI-4.8 while the reflector of the Jules Horowitz Reactor (JHR) was considered as the hosting environment of the transforming device. The results obtained suggest that elements with important inelastic neutron scattering could be chosen at a first level as being able to modify the prevailing neutron spectrum towards the desired direction. The factors which are important for an effective inelastic scatterer comprise density and inelastic microscopic cross section, as well as the energy ranges where inelastic scattering occurs. All the above factors have been separately examined in order to suggest potential device materials, able to locally produce SFR neutron spectrum imitation in a thermal MTR.